Sol-gel synthesis of lithium doped mesoporous bioactive glass nanoparticles and tricalcium silicate for restorative dentistry: Comparative investigation of physico-chemical structure, antibacterial susceptibility and biocompatibility - Simila, Hazel O.; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2023)
The sol-gel method for production of mesoporous bioactive glass nanoparticles (MBGNs) has been adapted to synthesize tricalcium silicate (TCS) particles which, when formulated with other additives, form the gold standard for dentine-pulp complex regeneration. Comparison of TCS and MBGNs obtained by sol-gel method is critical considering recent failure of one of the first ever clinical trials of sol-gel BAG as pulpotomy materials in children. Moreover, although lithium (Li) based glass ceramics have been long used as dental prostheses materials, doping of Li ion into MBGNs for targeted dental applications is yet to be investigated. The fact that lithium chloride benefits pulp regeneration in vitro also makes this a worthwhile undertaking. Therefore, this study aimed to synthesize TCS and MBGNs doped with Li by sol-gel method, and perform comparative characterizations of the obtained particles. TCS particles and MBGNs containing 0,5,10 and 20% Li were synthesized and particle morphology and chemical structure determined. Powder concentrations of 15mg/10ml were incubated in artificial saliva (AS), Hank’s balanced saline solution (HBSS) and simulated body fluid (SBF), at 37℃ for 28 days and pH evolution and apatite formation, monitored. Bactericidal effects against S. aureus and E.coli, as well as possible cytotoxicity against MG63 cells were also evaluated through turbidity measurements. MBGNs were confirmed to be mesoporous spheres ranging in size from 123nm - 194nm, while TCS formed irregular nano-structured agglomerates whose size was generally larger and variable. From ICP-OES data, extremely low Li ion incorporation into MBGNs was detected. All particles had an alkalinizing effect on all immersion media, but TCS elevated pH the most. SBF resulted in apatite formation for all particle types as early as three days, but TCS appears to be the only particle to form apatite in AS at a similar period. Although all particles had an effect on both bacteria, this was pronounced for undoped MBGNs. Whereas all particles are biocompatible, MBGNs have better antimicrobial properties while TCS is associated with greater bioactivity. Synergizing these effects in dental biomaterials may be a worthwhile undertaking and realistic data on bioactive compounds targeting dental application may be obtained by varying the immersion media.